IMPROVING INTERCULTURAL COMMUNICATIVE COMPETENCE THROUGH ADAPTIVE METHODS IN TEACHING ENGLISH FOR CADETS - Murakayeva Shakhnoza Khayrullayevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Abstract: In an increasingly globalized world, intercultural communicative competence (ICC) is essential for military cadets who must engage with diverse cultures during international operations. This article explores the implementation of adaptive methods in teaching English to cadets, focusing on enhancing their ICC. We examine the unique challenges faced by cadets in acquiring English language skills and propose adaptive strategies that cater to their specific needs, ultimately fostering more effective intercultural communication.